The Role of Triple Bottom Line in Improving Firm Value through Good Corporate Governance - Rita Rosalina; Muhammad Ja'far Shodiq (Jurnal Dinamika Akuntansi, 2025)
Purposes: This study analyzes the influence of good corporate governance on company value, using the triple bottom line as an intervening variable.Methods: This study uses a quantitative approach, using research data in the form of secondary data from annual reports and sustainability reports. The population is companies with the Kompas 100 index for the 2020-2023 period . The sampling technique used is non-random sampling with a purposive sampling method. The data analysis technique is multiple linear regression analysis.Findings: This study’s results indicate that the independent board of commissioners and the audit committee positively and significantly affect Firm Value. The triple bottom line can mediate this relationship.Novelty: This study is unique in adding a new variable, the triple bottom line, as a mediating variable between good corporate governance and firm value. Previous studies have yet to examine the variables of good corporate governance, triple bottom line, and Firm Value directly. Therefore, this study wants to explore the three variables together.